Challenges in the treatment of gastric cancer in the older patient. (April 2020) - Joharatnam-Hogan, Nalinie; Shiu, Kai Keen; Khan, Khurum
Highlights: Gastric cancer is largely a disease of the older patient. Current guidelines are predominantly based on clinical trials in younger, fit patients. An individualised approach to management of the older patient is required. Using functional age rather than chronological age may improve outcomes in elderly. Summary of current evidence extrapolated from trial data of optimum management. Abstract: Gastric cancer is considered an age-related disease, with the majority of new cases in the UK diagnosed in individuals over the age of 75. At present most guidance related to the management of gastric cancer is based on trials undertaken in the fit, younger patient. Historically the elderly have been underrepresented in clinical trials, which frequently have a restricted inclusion to an upper age limit of 75. The European Society for Medical Oncology (ESMO) recommends use of a geriatric assessment to determine functional age when initiating treatment in elderly patients with gastric cancer, which has been shown to be a better predictor of treatment response than chronological age. The physiological changes that occur with age, including reduced organ function and pharmacokinetic and pharmacodynamic variability, together with impaired functional status, necessitate a more individualised approach to treatment decisions in the older patient to provide them with the same advantages from radical treatment and palliative chemotherapy as younger patients. This review summarises the current evidence extrapolated from trial data on how best to optimise treatment for elderly patients with gastric cancer.